Anxiety and Game-Based Formative Assessment Platform Performance among Tertiary Level Students - Kamilia Mohd Arif, Fatin; Zaireen Zubir, Natasha; Mohamad, Maslawati; Md Yunus, Melor (International Journal of Engineering and Technology, 2018)
Kahoot is a gamification which embarks on the initiative of learning through play. In this study, personal achievements are often focused on when the respondents participated in a series of Kahoot. However, it neglects anxiety as a contributing factor to one’s performance. Therefore, this study was aimed to investigate the role of anxiety among tertiary level students. The Kahoot formative evaluations were conducted among Year 3 Teaching English as a Second Language (TESL) students. There were 46 students of them, aged between 20 to 24 years old. A 20-item questionnaire adapted from Test Anxiety Inventory was used to report the effects of anxiety to students’ physical, mental and emotional construct. The findings indicate that majority of the respondents had an after-feeling that they could have performed better if they revised the lecture notes and other related materials prior to the Kahoot session. The respondents also believed that they could perform at par with the others if they could manage their test anxiety level. The major implication derived from this study is teachers need to be made aware of their students’ feelings especially anxiety in integrating Kahoot as a formative assessment in English as a second language classroom.